Mixed‐method research protocol: Development and evaluation of a nursing intervention in patients discharged from the intensive care unit - Cecilia Cuzco; Pedro Castro Rebollo; Raquel Marín Pérez; Ana Isabel Núñez Delgado; Marta Romero García; M. Antonia Martínez Momblan; Dolors Estrada Reventós; Gemma Martínez Estalella; Pilar Delgado‐Hito (Wiley, 2021)
Abstract Aim (a) To understand patients' lived experience at intensive care unit (ICU) discharge and (b) to evaluate the impact of a nursing empowerment intervention (NEI) on patients' anxiety and depression levels at ICU discharge. Design A mixed‐methods approach will be applied. Methods In the qualitative phase, the hermeneutic phenomenological method will be used. Participants will be patients from three university hospitals who will be selected by purposive sampling. Data will be gathered through in‐depth interviews and analysed using content analysis. The qualitative data obtained will be employed to develop the nursing intervention. Subsequently, a multicenter, parallel‐group, experimental pre‐test/post‐test design with a control group will be used to measure the effectiveness of the nursing empowerment intervention in the quantitative phase by means of the Hospital Anxiety and Depression Scale (HADS). Simple random probabilistic sampling will include 172 patients in this phase.